Free-riding on Communication: An Experimental Study - Ola Andersson; Håkan J. Holm (Lund University, School of Economics and Management, Department of Economics, 2011)
This paper experimentally investigates free-riding behavior on communication cost in a coordination game and finds strong indications of such free-riding. Firstly, the subjects tend to wait for others to send a message when communication is costly, which does not happen when communication is costless. Secondly, the proportion of games where no communication takes place is much higher when communication is costly compared to when it is free. Thirdly, the form of communication also strongly suggests free-riding.
Keywords: C72; C91; D43; 330; Free-riding; Communication; Coordination